Lipid Oxidation In Oil-In-Water Emulsions: A Mini Review - Sri Haryani Anwar (Agricultural Faculty, 2015)
Emulsion technology has been emerged into food industries widely. Researches in emulsion and its application have been done intensively particularly to understand emulsion behavior in relation to its stability. Stability of emulsion indicates stability of food products therefore attempt to identify the causes of instability increases. This mini review underlines lipid oxidation in oil in water emulsion including emulsion definition, factors involved in determining the rate of lipid oxidation, common cause of oxidative instability and some case examples of lipid oxidation in emulsion.